Directly‐Deposited Ultrathin Solid Polymer Electrolyte for Enhanced CO2 Electrolysis. Issue 12 (4th January 2023) - Adnan, Muflih A.; Shayesteh Zeraati, Ali; Nabil, Shariful Kibria; Al‐Attas, Tareq A.; Kannimuthu, Karthick; Dinh, Cao‐Thang; Gates, Ian D.; Kibria, Md Golam
Abstract: The economic viability of carbon dioxide electroreduction (CO2 R) relies on improved performance accompanied by scalable system design. Membranes are commonly used for the separation of reduction and oxidation products as well as to provide a suitable micro‐environment for CO2 R. Commercial membranes often address only one of the key challenges in CO2 R: either they offer a suitable micro‐environment for CO2 R (e.g., anion exchange membrane) or suppress carbonate cross‐over (e.g., cation exchange membrane and bipolar membrane). This work presents a cation‐infused ultrathin (≈3 µm) solid polymer electrolyte (CISPE) that concomitantly addresses both challenges via a bidirectional ion transport mechanism and suppressed cathode flooding. This directly‐deposited CISPE (that substitutes the commonly used pre‐made membrane) enables record high full‐cell energy efficiency of 28% at 100 mA cm −2 for one‐step CO2 electrolysis to ethylene (C2 H4 ) with ≈110 h of stable operation. This translates into a record low energy cost of 290 GJ per ton C2 H4 for the end‐to‐end process (i.e., CO2 capture and electroreduction, carbonate regeneration, CO2 separation from anode and cathode streams) in a membrane electrode assembly CO2 R. The present work offers a versatile design paradigm for functional polymer electrolytes, opening the door to stable, and efficient electrolysis of high‐value feedstock chemicals and fuels using low‐cost catalysts. Abstract : A cation infused solid polymer electrolyte (CISPE) is designed for enhanced CO2 electrolysis. The CISPE is a directly deposited ultra‐thin solid polymer electrolyte (≈3 µm) that offers a suitable micro‐environment and enhanced cell stability. This is the first report on ultra‐thin SPEs for CO2 electroreduction that removes the need for a standalone membrane in a membrane electrode assembly cell for CO2 electrolysis.